A Survey of Real-time Simulation and Hardware-in-the-loop Technology - Chen, Jingyu (Transactions on Computer Science and Intelligent Systems Research, 2024)
This paper introduces the definition and background of real-time simulation and hardware-in-the-loop technology, and explains the concept, development process and application field of real-time simulation and hardware-in-the-loop technology, as well as its importance and advantages in practical applications. The research methods and technologies for real-time simulation and hardware-in-the-loop technology include commonly used methods and technologies for model establishment, control algorithm design, system integration, and experimental verification. For the application of real-time simulation and hardware-in-the-loop technology, specific cases in different fields are also listed, such as the design of distribution automation terminal in the kernel, the research of virtual test system of hardware-in-the-loop for unmanned vehicles, etc. Finally, the current challenges of real-time simulation and hardware-in-the-loop technology are stated, and the future development trend of the technology is summarized.